Evaluability assessment of drug prevention programs - Craig W. LeCroy; Matt Ignacio (Academia Mental Health & Well-Being)
Evaluability assessments are being used by organizations more frequently to improve the effective outcomes of programs. This study presents a model for examining the evaluability of 11 community-based drug misuse prevention programs funded by a state government office. This paper aims to provide further understanding and an overview of the application of evaluability assessment. It demonstrates the use of The Five-Tiered Approach to Evaluation as a conceptual framework to assess the preparedness of these programs for outcome evaluation and pinpoint areas that require additional development prior to outcome evaluation. The research focuses on the adoption of an evaluation methodology for use by a government agency to assist in drug prevention programs as they move toward outcome evaluation. The results found six programs ready for outcome evaluation, notwithstanding the wide range in program readiness revealed by the findings. The absence of clear, quantifiable goals, insufficient capacity for data gathering, and poor community engagement are among the main barriers to beginning an outcome evaluation. To enhance assessment efforts, recommendations include educating program personnel on how to set reasonable goals, enhancing data gathering techniques, and cultivating community connections. This study emphasizes how crucial evaluability assessment is.